Acquisition of portuguese as L2 by veneuelan children in a cross-border context: code-switching in the classroom - Lemos, David Sena; Del Re, Alessandra [UNESP] (Univ Estadual Campinas, Inst Estudos Linguagem, 2022)
This work is part of a broader study on the acquisition of Brazilian Portuguese (PB) as a second language (L2) in a school setting on Brazil's northern border (Pacaraima) and Venezuela's southern border (Santa Elena de Uairen). We analyzed the speech of three Venezuelan four-year-old children acquiring BP, in particular the issue of code-switching, by three 4-year-old Venezuelan children interacting with native speakers of BP in the classroom (Early Childhood Education). Eighteen sessions, between 30 and 45 minutes, were filmed and later transcribed using the CHAT/CLAN tool. This study is both longitudinal and qualitative. To analyse the data, we used a dialogic and discursive approach that seeks to understand how language and the production of meaning work. Both occur in the relationships undertaken among subjects, with other discourses, in which sociocultural and ideological aspects are involved, in certain discursive contexts (BAKHTIN; VOLOCHINOV, 2014 [1929], SALAZAR-ORVIG, 2010; SALAZAR-ORVIG et al., 2010, Del Re et al., 2014a). The research findings reveal that children code-switch in a variety of ways during specific discursive events at school, especially when motivated by external factors such as the topic of interaction or prior experience with distinct speech genres which include children's songs and tales.
Keywords: Bilingualism; Code-switching; Acquisition/learning of Portuguese as an L2; Child Education